HDTV : assessing an innovation at three points in time - Elias, Jaan; Sudhir, K. ([London] : SAGE, 2016)
When colour television reached the mass market, many broadcasters dreamed of another goal - to improve the television picture so that it would rival that of motion pictures. This study examines the development of HDTV at three particular points in time.
Originally Published in: Elias, J., & Sudhir, K. (2007). HDTV: Assessing an Innovation at Three Points in Time. 07-012. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; High definition television; Technological innovations -- Economic aspects -- Case studies; Creative ability in business -- Case studies